Tree diseases determined by the reporting, prognostic and diagnostic service for forests in Slovenia 1982-2012 - Ogris, Nikica (Acta silvae et ligni, 2013)
The Reporting, Prognostic and Diagnostic (RPD) service for forests is a legal forest protection organization in Slovenia and part of the public forest service. The aim of our study was to analyse RPD reports from 1982 to 2012. We analysed 120 reports that contained 992 records of tree diseases encompassing 189 species and genera. The most frequently recorded were foliage diseases (351 records, 42 species), needle diseases (162 records, 23 species), rots (111 records, 56 species), cankers (73 records, 9 species), and shoot diseases (72 records, 14 species). Ten most frequently recorded species were the following fungi: Erysiphe alphitoides, Lophodermium spp., Cryphonectria parasitica, Rhytisma acerinum, Sawadaea bicornis, Diplodia pinea, Hymenoscyphus pseudoalbidus, Mycosphaerella pini, Blumeriella jaapii, and Cronartium ribicola.
Keywords: varstvo gozdov; Slovenia; Slovenija; poročila; bolezni drevja; analize